Outside Back Cover: Volume 3 Issue 3. Issue 3 (24th August 2022) - Lv, Wenkun; Liu, Zhaoxin; Li, Zheng; Han, Zhifei; Yang, Yongrui; Li, Qi; Qiao, Yali; Song, Yanlin
Abstract : Outside back cover image : This work reports an elastomer‐assisted strategy to improve the functional pattern integration density with a pre‐strain elastic substrate. This strategy overcomes the limitations on pattern integration density and enables the simultaneous improvement of resolution in line width and interval. The ratio of line width to interval is approaching 1:1. The integration density of the printed patterns with submicron precision reaches 1932 lines on a substrate of 0.5 cm 2 . This work provides a promising strategy for the fabrication of high‐precision and high‐integrated optoelectronic devices. (DOI: 10.1002/smm2.1104 )